2014
DOI: 10.1002/2014ja020066
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and energetic particle observations in Jupiter's deep tail near the magnetopause

Abstract: Jupiter's nightside magnetosphere stretches out into an extensive magnetotail. New Horizons observed continuously over 1 AU down Jupiter's tail, far more than any other spacecraft. Previously, Voyager 2 showed signatures of the tail as far as 4 AU distance from Jupiter. We combine data from New Horizons' charged particle instruments: Solar Wind Around Pluto, measuring plasma ions (21–7800 eV/Q), and Pluto Energetic Particle Spectrometer Science Investigation, measuring energetic ions and electrons (0.03–1.6 Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, PEPSSI's nominal electron measurement is based on single SSDs without coincidences behind a 1 μm aluminum flashing (to suppress ions having energies below a few hundred keV nucleon −1 ) and assumes that the electrons are collimated by the instrument aperture (McNutt et al 2008). This is an effective electron measurement technique in the presence of sufficient electron foreground, such as we observed at Jupiter (McNutt et al 2007;Haggerty et al 2009;Kollmann et al 2014). Cosmic rays are energetic enough to pass through the flashing, the collimator fins, the walls of the instrument, and indeed even the complete body of the spacecraft, providing a large geometric factor.…”
Section: A1 Hardwarementioning
confidence: 99%
“…However, PEPSSI's nominal electron measurement is based on single SSDs without coincidences behind a 1 μm aluminum flashing (to suppress ions having energies below a few hundred keV nucleon −1 ) and assumes that the electrons are collimated by the instrument aperture (McNutt et al 2008). This is an effective electron measurement technique in the presence of sufficient electron foreground, such as we observed at Jupiter (McNutt et al 2007;Haggerty et al 2009;Kollmann et al 2014). Cosmic rays are energetic enough to pass through the flashing, the collimator fins, the walls of the instrument, and indeed even the complete body of the spacecraft, providing a large geometric factor.…”
Section: A1 Hardwarementioning
confidence: 99%
“…It had a unique trajectory that allowed it to observe Jupiter's extended magnetotail and crossed the magnetopause 16 times between 1,654 and 2,429 Jovian radii (R J ) on the dusk flank (McComas et al, 2007). Even at 1 astronomical unit (AU) from Jupiter, the magnetosheath and magnetotail populations were distinct, with the magnetosheath having more protons and helium ions while having fewer oxygen and sulfur ions (Haggerty et al, 2009;Kollmann et al, 2014). The energetic particles measured by the Pluto Energetic Particle Spectrometer Science Investigation (PEPSSI) (McNutt et al, 2008) found a less distinct transition, which Kollmann et al (2014) posited was the result of very brief magnetic connection events that thread the boundary and only allow the fastest particles to cross.…”
Section: Introductionmentioning
confidence: 99%
“…Even at 1 astronomical unit (AU) from Jupiter, the magnetosheath and magnetotail populations were distinct, with the magnetosheath having more protons and helium ions while having fewer oxygen and sulfur ions (Haggerty et al, 2009;Kollmann et al, 2014). The energetic particles measured by the Pluto Energetic Particle Spectrometer Science Investigation (PEPSSI) (McNutt et al, 2008) found a less distinct transition, which Kollmann et al (2014) posited was the result of very brief magnetic connection events that thread the boundary and only allow the fastest particles to cross. From these distant crossings, Ebert et al (2010) found that the energy per charge of the plasma had the general trend of decreasing between exiting the magnetotail to reentering it.…”
Section: Introductionmentioning
confidence: 99%
“…Energetic particle measurements were also made over the New Horizons tail passage by the Pluto Energetic Particle Spectrometer Science Investigation (PEPPSI) instrument [ McNutt et al ., ]. Energetic particle observations [ McNutt et al ., ; Haggerty et al ., ; Hill et al ., ; Kollmann et al ., ] collectively showed multiple species, compositional variation, velocity dispersions, intermittent ~3 day periodicities, and particle anisotropies. Several dispersive events drive the largest variability seen in energetic particles and confirm that there is at least intermittent magnetic connection between tail and boundary layer and between boundary layer and magnetosheath.…”
Section: Introductionmentioning
confidence: 99%
“…Several dispersive events drive the largest variability seen in energetic particles and confirm that there is at least intermittent magnetic connection between tail and boundary layer and between boundary layer and magnetosheath. Differences between the tail and deep magnetosheath were much less clear in the energetic particles than in the plasma data, and while energetic protons and helium ions are more abundant in the magnetosheath and energetic electrons, oxygen, and sulfur ions are more abundant in the tail, their collective variability is larger than any consistent difference between the two [ Kollmann et al ., ].…”
Section: Introductionmentioning
confidence: 99%